Global challenges and strategic disruptors in Asian businesses and economies - Ordonez de Pablos, Patricia 1975-; Lytras, Miltiadis D. 1973- (IGI Global, 2021)
"The book presents a collection of chapters exploring and discussing the state-of-the-art, emerging topics, challenges and success factors in business, big data, innovation and technology in Asia, exploring how IoT, big data and AI can provide solutions for global challenges and companies"--
Description based on title screen (IGI Global, viewed 09/19/2020)
Keywords: Business enterprises / Technological innovations; Disruptive technologies; Economic development / Technological innovations; Information technology / Economic aspects; Technological innovations / Economic aspects; Economic development / Technological innovations / Asia; Technological innovations / Economic aspects / Asia; Business enterprises / Technological innovations / Asia; Information technology / Economic aspects / Asia; Disruptive technologies / Asia